Management Information Systems and the Efficiency of Elementary School Administration: A Literature Review Based on Evidence-Based Research on Integrated Systems - Ramadhan Maruta Pradana; Devi Purnamasari Sasongko; Esa Mariya Puspitasari; Yurika Fauzia Wardhani; Andi Kristanto; Syunu Trihantoyo (Universitas Negeri Malang, 2026)
Abstract: This study presents a systematic literature review examining the effectiveness of Management Information Systems (MIS) in improving the efficiency and accountability of elementary school management. The review followed the PRISMA 2020 guidelines. A structured search across Scopus, Web of Science, IEEE Xplore, ScienceDirect, and Google Scholar identified 186 records. After duplicate removal, screening, and eligibility assessment, 24 empirical studies published between 2015 and 2025 were included. The findings indicate that MIS implementation consistently enhances administrative efficiency, improves data accuracy, accelerates reporting processes, and strengthens managerial accountability. Integrated MIS platforms were associated with streamlined workflows, reduced documentation redundancy, and improved institutional transparency. However, the effectiveness of MIS adoption remains influenced by system integration, technological infrastructure, digital literacy, leadership support, and organisational readiness. Persistent barriers include limited internet connectivity, inadequate hardware, user competency gaps, and resistance to technological change. Overall, MIS functions as a strategic enabler of evidence-based governance in elementary education. Sustainable benefits require integrated system design, infrastructure readiness, and continuous capacity-building initiatives. Abstrak: Penelitian ini menyajikan tinjauan pustaka secara sistematis yang mengkaji efektivitas Sistem Informasi Manajemen (SIM) dalam meningkatkan efisiensi dan akuntabilitas pengelolaan sekolah dasar. Tinjauan ini mengikuti pedoman PRISMA 2020. Pencarian terstruktur di Scopus, Web of Science, IEEE Xplore, ScienceDirect, dan Google Scholar mengidentifikasi 186 artikel. Setelah proses seleksi duplikat, penyaringan, dan penilaian kelayakan, 24 studi empiris yang diterbitkan antara tahun 2015 dan 2025 digunakan dalam proses analisis. Temuan menunjukkan bahwa penerapan Sistem Informasi Manajemen (SIM) secara konsisten meningkatkan efisiensi administratif, memperbaiki akurasi data, mempercepat proses pelaporan, dan memperkuat akuntabilitas manajerial. Platform SIM terintegrasi dikaitkan dengan alur kerja yang lebih efisien, pengurangan redundansi dokumentasi, dan peningkatan transparansi kelembagaan. Namun, efektivitas penerapan Sistem Informasi Manajemen (SIM) tetap dipengaruhi oleh integrasi sistem, infrastruktur teknologi, literasi digital, dukungan kepemimpinan, dan kesiapan organisasi. Hambatan yang terus berlanjut meliputi konektivitas internet yang terbatas, perangkat keras yang tidak memadai, kesenjangan kompetensi pengguna, serta penolakan terhadap perubahan teknologi. Secara keseluruhan, SIM berfungsi sebagai pendorong strategis bagi tata kelola berbasis bukti di bidang pendidikan dasar. Untuk memperoleh manfaat yang berkelanjutan, diperlukan desain sistem yang terintegrasi, kesiapan infrastruktur, serta inisiatif pengembangan kapasitas yang berkelanjutan.